Metrical thresholds of an English verse - Tarlinskaya, Marina; Teterina, Lilia (Literatūra, 1974)
Degree of metricity of an English verse of a transitory type, from syllabo-tonic (iambic pentameter) towards purely syllabic (decasyllabic) verse is determined. Donne’s "Satyres" represent such a transitory verse form. First, unquestionably metrical iambic pentameter is analysed according to a number of parameters and its thresholds are determined, the latter being figures characterizing the maximum loosening of verse form, still permitted by the metre norm. Next, Donne’s "Satyres" are analysed according to the same parameters; their verse is shown to deviate from the outlined iambic thresholds in many ways. Finally, speech models of quasi-iambic pentameter and quasi-syllabic verse are analysed, again according to the same parameters as real iambus, quasi-iambic pentameter being those "iambic" segments which chance to occur in prose, while quasi-syllabic verse - decasyllabic syntagmatic prose segments. The comparison of real English iambic pentameter, the "Satyres" verse and quasi-iambus helps to determine the tendencies of the "Satyres" verse, while the comparison of real iambic pentameter, the "Satyres" and quasi-syllabic verse models makes it possible to determine the place of the "Satyres" between two opposite poles. Thresholds of real iambus being taken for 0 per cent, those of quasi-syllabic verse model for 100 per cent, the "Satyres" are found to have covered 45.5 per cent of the distance from iambic pentameter towards purely syllabic verse.